The crystal structure of (S, R p)-4–benzhydrylideneamino-12-(4-tert-butyl oxazolin-2-yl)[2.2]paracyclophane, C36H36N2O - Chen Zhen; Sun Yanwen; Chen Chao; Xu Nuo; Wang Xiaozhong; Li Sijun (Zeitschrift für Kristallographie - New Crystal Structures, 2023)
C36H36N2 ${C}_{36}{H}_{36}{N}_{2}$ O, orthorhombic, P212121 ${2}_{1}{2}_{1}{2}_{1}$ (no. 19), a = 11.849(2) Å, b = 14.373(3) Å, c = 17.183(3) Å, V = 2926.4(10) Å3 ${\mathrm{\mathring{\text{A}}}}^{3}$ , Z = 4, Rgt ${R}_{gt}$ (F) = 0.0514, w Rref ${R}_{ref}$ (F2 ${F}^{2}$ ) = 0.1272, T = 296(2) K.